Difference between revisions of "008A Sample Final A, Question 12"
Jump to navigation
Jump to search
(Created page with "'''Question: ''' Find and simplify the difference quotient <math>\frac{f(x+h)-f(x)}{h}</math> for f(x) = <math>\frac{2}{3x+1}</math> {| class="mw-collapsible mw-collapsed"...") |
|||
(One intermediate revision by the same user not shown) | |||
Line 2: | Line 2: | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | !Foundations | + | !Foundations: |
|- | |- | ||
|1) f(x + h) = ? | |1) f(x + h) = ? | ||
Line 10: | Line 10: | ||
|Answer: | |Answer: | ||
|- | |- | ||
− | |1) | + | |1)<math>f(x + h) = \frac{2}{3(x + h) + 1}</math>. |
|- | |- | ||
− | |2) The numerator is <math>\frac{2}{3(x + h) + 1} - \frac{2}{3x + 1}</math> so the first step is to simplify this expression. This then allows us to eliminate the 'h' in the denominator. | + | |2) The numerator of the difference quotient is <math>\frac{2}{3(x + h) + 1} - \frac{2}{3x + 1}</math> so the first step is to simplify this expression. This then allows us to eliminate the 'h' in the denominator. |
|} | |} | ||
Line 18: | Line 18: | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | ! Step 1: | + | !Step 1: |
|- | |- | ||
|The difference quotient that we want to simplify is <math>\frac{f(x + h) - f(x)}{h} = \left(\frac{2}{3(x + h) + 1} - \frac{2}{3x + 1}\right) \div h</math> | |The difference quotient that we want to simplify is <math>\frac{f(x + h) - f(x)}{h} = \left(\frac{2}{3(x + h) + 1} - \frac{2}{3x + 1}\right) \div h</math> | ||
Line 24: | Line 24: | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | ! Step 2: | + | !Step 2: |
|- | |- | ||
|Now we simplify the numerator: | |Now we simplify the numerator: | ||
|- style = "text-align:center;" | |- style = "text-align:center;" | ||
| | | | ||
− | <math>\begin{array}{rcl} | + | ::<math>\begin{array}{rcl} |
− | \frac{f(x + h) - f(x)}{h} &=& \left(\frac{2}{3(x + h) + 1} - \frac{2}{3x + 1}\right) \div h\\ | + | \displaystyle{\frac{f(x + h) - f(x)}{h}} &=& \displaystyle{\left(\frac{2}{3(x + h) + 1} - \frac{2}{3x + 1}\right) \div h}\\ |
− | + | & & \\ | |
− | &=& \frac{2(3x + 1) -2(3(x + h) + 1)}{h(3(x + h) + 1)(3x + 1))} | + | &=& \displaystyle{\frac{2(3x + 1) -2(3(x + h) + 1)}{h(3(x + h) + 1)(3x + 1))}} |
\end{array}</math> | \end{array}</math> | ||
|} | |} | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | ! | + | !Step 3: |
|- | |- | ||
|Now we simplify the numerator: | |Now we simplify the numerator: | ||
|- style = "text-align:center;" | |- style = "text-align:center;" | ||
| | | | ||
− | <math>\begin{array}{rcl} | + | ::<math>\begin{array}{rcl} |
− | \frac{2(3x + 1) -2(3(x + h) + 1)}{h(3(x + h) + 1)(3x + 1))} & = & \frac{6x + 2 - 6x -6h -2}{h(3(x + h) + 1)(3x + 1))}\\ | + | \displaystyle{\frac{2(3x + 1) -2(3(x + h) + 1)}{h(3(x + h) + 1)(3x + 1))}} & = & \displaystyle{\frac{6x + 2 - 6x -6h -2}{h(3(x + h) + 1)(3x + 1))}}\\ |
− | & = & \frac{-6}{(3(x + h) + 1)(3x + 1))} | + | & & \\ |
+ | & = & \displaystyle{\frac{-6}{(3(x + h) + 1)(3x + 1))}} | ||
\end{array}</math> | \end{array}</math> | ||
|} | |} | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | ! Final Answer: | + | !Final Answer: |
|- | |- | ||
|<math>\frac{-6}{(3(x + h) + 1)(3x + 1))}</math> | |<math>\frac{-6}{(3(x + h) + 1)(3x + 1))}</math> | ||
|} | |} | ||
[[008A Sample Final A|<u>'''Return to Sample Exam</u>''']] | [[008A Sample Final A|<u>'''Return to Sample Exam</u>''']] |
Latest revision as of 22:59, 25 May 2015
Question: Find and simplify the difference quotient for f(x) =
Foundations: |
---|
1) f(x + h) = ? |
2) How do you eliminate the 'h' in the denominator? |
Answer: |
1). |
2) The numerator of the difference quotient is so the first step is to simplify this expression. This then allows us to eliminate the 'h' in the denominator. |
Solution:
Step 1: |
---|
The difference quotient that we want to simplify is |
Step 2: |
---|
Now we simplify the numerator: |
|
Step 3: |
---|
Now we simplify the numerator: |
|
Final Answer: |
---|